Association of Caribbean States : united in the greater Caribbean (ACS Port of SpainTT, 2003)
Includes country profiles. Focuses on issues of major concern to ACS such as regional integration, vulnerability to disasters, globalization, trade, privatisation, tourism, air transport, sustainable economic development, piracy, coral reef degradation, aquaculture and labour markets.
9th Ministerial Meeting November 2003. 4th Summit and 10th Ministerial Meeting February 2004.